Reconstruction of Pesantren Literature Through A. Mustofa Bisri’s Short Story Collection - Lamri Lamri; Bilqis Salsabila Safa; Leonita Leonita; Moh. Khalid Hasan (JENTERA: Jurnal Kajian Sastra, 2025)
The term "Pesantren Literature" remains entangled in a definitional ambiguity that tends to focus only on local aspects or religious labels. This study aims to reconstruct the definition, characteristics, and traits of pesantren literature ontologically and epistemologically through a structural analysis of short stories. Using a qualitative descriptive method with a sociological-structural dialectic approach, this study analyzes short-story anthologies by A. Mustofa Bisri. The analysis was conducted by combining the analysis of intrinsic (text) and extrinsic (authorial context) elements. Data analysis technique using the theory of Miles and Huberman. The results of the study indicate that Islamic boarding school literature is a manifestation of prophetic aesthetics built on traditional Islamic epistemology. Intrinsically, the narrative structure accommodates the logic of karomah, transcendental themes, and hybrid characters. Extrinsically, this work is validated by the author's dual authority (Double Legitimacy) as a kiai and a pesantren writer, as well as the psychology of tuma'ninah which makes the work a therapeutic literature. This study concludes the model of prophetic structural realism, namely a literary genre that not only portrays the social reality of Islamic boarding schools, but transcends it into a religious humanist life ethic. Abstrak Istilah "Sastra Pesantren" tetap terjerat dalam ambiguitas definisi yang cenderung hanya berfokus pada aspek lokal atau label agama. Penelitian ini bertujuan untuk merekonstruksi definisi, karakteristik, dan ciri-ciri sastra pesantren secara ontologis dan epistemologis melalui analisis struktural cerpen. Dengan menggunakan metode deskriptif kualitatif dengan pendekatan dialektika sosiologis-struktural, penelitian ini menganalisis antologi cerpen karya A. Mustofa Bisri. Analisis dilakukan dengan menggabungkan analisis unsur intrinsik (teks) dan ekstrinsik (konteks penulis). Teknik analisis data menggunakan teori Miles dan Huberman. Hasil penelitian menunjukkan bahwa literatur pondok pesantren merupakan wujud estetika profetik yang dibangun di atas epistemologi Islam tradisional. Secara intrinsik, struktur naratif mengakomodasi logika karomah, tema transendental, dan karakter hibrida. Secara ekstrinsik, karya ini divalidasi oleh otoritas ganda penulis (Legitimasi Ganda) sebagai penulis kiai dan pesantren, serta psikologi tuma'ninah yang menjadikan karya tersebut sebagai literatur terapeutik. Penelitian ini menyimpulkan model realisme struktural profetik, yaitu genre sastra yang tidak hanya menggambarkan realitas sosial pondok pesantren, tetapi melampauikannya menjadi etos hidup humanis religius.